Analisis Pembelajaran PAI melalui Implementasi Kurikulum Merdeka Belajar di SMPN 1 Kabuh - Wafa, M. Aliyul; Roziqin, Muhamad Khoirur; Yadha, Nurul Isma (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This research aims to evaluate the Implementation of the Independent Learning Curriculum (IKMB) in Islamic Religious Education (PAI) learning at SMPN 1 Kabuh. The methodology used is descriptive qualitative with data collection through observation, interviews and documentation, as well as data analysis through collection, reduction, presentation and drawing conclusions. The research results show that PAI learning with KMB produces differentiated learning, with students being the center of learning and the learning process adapted to their learning styles and abilities. Apart from that, PAI learning with KMB increases learning effectiveness by organizing good material, effective communication, mastery of material by teachers and student enthusiasm, positive attitudes towards students, giving fair grades, flexibility in learning approaches, and satisfactory learning results. In conclusion, the Merdeka Belajar Curriculum brings positive changes in PAI learning at SMPN 1 Kabuh by freeing teachers and students in the learning process and producing better learning effectiveness.